PENGARUH PENYULUHAN TENTANG EKSTERNAL DOUCHING VAGINA TERHADAP PENGETAHUAN DAN SIKAP REMAJA - Debbiyatus Sofia (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2016)
External vaginal douching is cleaning the outside of the vagina activity with certain materials. Activities outside of the vagina cleans indiscretion can worsen the condition of the vagina, but it also can increase the risk of sexually transmitted infections (STIs), inflammation of the vulva to inflammation of the vagina. This study aimed to determine the effect of external counseling about vaginal douching on knowledge and attitudes of teenagers. Design of this research is pre experimental design